Analysis Of The Validity Of Divorce Through Social Media From The Perspective Of Kitabun Nikah And Indonesian Positive Law - Abrar, Muhammad Tajally Abrar; Mutthiah; Maulidiya Rahmah; Anwar Hafidzi (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This study analyzes the validity of divorce conveyed through social media from the perspective of Kitabun Nikah and Indonesian positive law. In Islam, marriage is a very strong contract, but problems in the household can lead to divorce. Talak, as an act of the husband dissolving the marriage bond, can be done verbally or in writing. In the digital era, social media such as WhatsApp, Facebook, and others have become common means of communication, including to convey divorce. The Kitabun Nikah recognizes written divorce under certain conditions, while Indonesian positive law, especially Law No. 1 of 1974 and the Compilation of Islamic Law (KHI), requires that divorce must be carried out in front of the Religious Court. This research uses a descriptive analysis method with a qualitative approach to examine the views of the two legal systems. The results show that although in Islamic fiqh divorce through social media can be considered valid under certain conditions, Indonesian positive law does not recognize it if it is not done in front of the court. This creates a mismatch between the practice of religious law and state regulations, resulting in the inability of couples to remarry or claim rights after divorce. Therefore, harmonization efforts between the two legal systems are needed to accommodate the interests of the community and ensure the public good.   Keywords- Talak, Social Media, Kitabun Nikah, Indonesian Positive Law     Abstrak Penelitian ini menganalisis keabsahan talak yang disampaikan melalui media sosial dari perspektif Kitabun Nikah dan hukum positif Indonesia. Dalam Islam, pernikahan merupakan akad yang sangat kuat, namun permasalahan dalam rumah tangga dapat berujung pada perceraian. Talak, sebagai tindakan suami yang membubarkan ikatan pernikahan, dapat dilakukan secara lisan maupun tulisan. Di era digital, media sosial seperti WhatsApp, Facebook, dan lainnya telah menjadi sarana komunikasi yang umum digunakan, termasuk untuk menyampaikan talak. Kitabun Nikah mengakui perceraian secara tertulis dengan syarat-syarat tertentu, sedangkan hukum positif Indonesia, khususnya UU No. 1 Tahun 1974 dan Kompilasi Hukum Islam (KHI), mensyaratkan perceraian harus dilakukan di depan Pengadilan Agama. Penelitian ini menggunakan metode analisis deskriptif dengan pendekatan kualitatif untuk mengkaji pandangan kedua sistem hukum tersebut. Hasil penelitian menunjukkan bahwa meskipun dalam fikih Islam perceraian melalui media sosial dapat dianggap sah dengan syarat-syarat tertentu, namun hukum positif Indonesia tidak mengakuinya jika tidak dilakukan di depan pengadilan. Hal ini menimbulkan ketidaksesuaian antara praktik hukum agama dan peraturan negara, yang berakibat pada ketidakmampuan pasangan untuk menikah kembali atau menuntut hak setelah perceraian. Oleh karena itu, diperlukan upaya harmonisasi antara kedua sistem hukum tersebut untuk mengakomodir kepentingan masyarakat dan menjamin kemaslahatan umum.   Kata Kunci- Talak, Media Sosial, Kitabun Nikah, Hukum Positif Indonesia